Analysis of Chinese Contemporary Theme Dance from the Perspective of Ecological Aesthetics: Taking The Spirit of the Sparrow as an Example - Chu, Xinying (International Journal of Social Sciences and Public Administration, 2024)
Ms. Yang Liping is a famous dancer and a national first-class actress. She is famous for peacock dance and known as "Peacock Princess". Ms. Yang Liping has many outstanding representative works, such as female solo dance "Spirit of the Bird", dance drama "Yunnan Image" and so on. Among them, the dance "Spirit of the Bird" won the gold medal of Chinese classic dance works in the 20th century. This article mainly analyzes the form and content of the dance "Spirit of the Bird" from the perspective of ecological aesthetics.